PENGARUH KONSERVATISME DAN KETIDAKTEPATAN WAKTU PENYAMPAIAN LAPORAN KEUANGAN TERHADAP EARNING RESPON COEFFICIENT - Astari Dianty (Media Mahardhika, 2020)
The purpose of this study is to analyze the relationship between conservatism and the inaccuracy of the delivery of financial statements with earning response coefficient on manufacturing companies listed on the Indonesia Stock Exchange. The population in this study is manufacturing companies listed on the Indonesia Stock Exchange in the period 2010-2012. The sample selection method used is the purposive sampling method. Based on purposive sampling, there were 91 companies included in the criteria during the 2010-2012 observation period, so there were 273 samples. The data analysis technique was done by SPSS Ver. 21. Based on the results of statistical tests, it was concluded that Conservatism and Inaccuracy in the delivery of financial statements have an influence on the Earning Response Coefficient. Based on these conclusions, the researcher suggests that the Issuer is more appropriate in presenting financial statements given the variable inaccuracy in the delivery of financial statements has an influence on the earnings response coefficient.